Instabilities in micro-contraction flows of semi-dilute CTAB and CPyCl solutions: rheology and flow instabilities - R. M. Matos (2019)
The flows of two semi-dilute surfactant solutions (CTAB and CPyCl) through several micro contractions/expansions are experimentally investigated, following an extensive rheological characterization in both shear and extensional flows. The shear rheology of the solutions shows strong shear thinning and shear banding, whereas Small Amplitude Oscillatory Shear and Capillary Break-up Extensional Rheometry indicate that they have high shear and extensional elasticities. Flow visualizations and micro-particle image velocimetry measurements show that the surfactant solutions exhibit three established types of flow patterns in contraction flows: Newtonian-like, asymmetric and disordered. Newtonian-like flow occurs at low flow rates and is preceded by a long transient flow in experiments starting from rest, which seems to be related to shear banding and the alignment of wormlike micelles. The asymmetric flow regime occurs at moderate flow rates and is characterized by an asymmetric upstream central jet with two adjacent vortices, features that change non-periodically, but slowly, in time. This flow pattern seems to be related with the high elasticity of the semi-dilute solutions. The disordered flow pattern is similar to the asymmetric flow in terms of broad characteristics, but the flow asymmetry changes with time much faster than in the asymmetric flow regime, resembling a chaotic-like flow. The disordered flow seems to be related with the breakdown of micellar structures. We concluded also that the flows in both the asymmetric and disordered flow regimes are globally stable in terms of flow patterns, but locally unstable in terms of flow characteristics, with power spectra of the velocity fluctuations having slopes that differ from those typically encountered in elastic turbulence. [GRAPHICS] .